Classroom Service Guide Using Kahoot Game During Covid 19 Pandemic - Siti Rahmi; Sopianto Sopianto; Riski Sovayunanto (International Journal of Educational Narratives, 2024)
Background. One of the guidance and counseling service programs that must be upgraded techniques or ways of service using computer and internet media is classical services.   Purpose. The purpose of the research is to find out in terms of feasibility in the development of a Classical Service Guide Using Kahoot Game which is applied to counseling teachers in schools. Method. Research conducted by researchers is a type of development research or Research and Development (R&D). Results. The results of validation from design experts show that the product design is in the very feasible category with a score of 53 at a percentage of 94.6%. the results of the material expert validation show that the material from the classical service guide using this kahoot game, is in the very feasible category with a score of 57 on the validation sheet and is at a percentage of 95%. Conclusion. So that in some of these results it can be understood that our service guide is very feasible to be used in the implementation of classical services by utilizing technological media such as this kahoot game. Furthermore, in the limited product trial, the results of this product trial were found to be in the very feasible category with a score obtained from the teacher response sheet of 99 with a percentage of 88.3%.